Hardiness sebagai Moderator: Pengaruh Peer Pressure terhadap Stres Akademik pada Siswa Boarding School - Syaka Athallya Varizqi; Tri Na'imah; Nur'aeni Nur'aeni; Gisella Arnis Grafiyana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Boarding schools implement a residential education system with intensive academic, social, and disciplinary demands, which may increase students academic stress. This study aims to examine hardiness as a moderator in the relationship between peer pressure and academic stress among boarding school students. This research employed a quantitative approach using a total sampling technique involving 114 students. The instruments used in this study were modified versions of the Perceived Peer Pressure Scale (PPPS; = 0.964), the Dispositional Resilience Scale-15 (DRS-15; = 0.953), and the Educational Stress Scale for Adolescents (ESSA; = 0.950). Data analysis was conducted using SmartPLS 4.0 software. The results indicate that hardiness does not moderate the effect of peer pressure on academic stress among boarding school students. These findings highlight the dominant role of social environmental factors in shaping academic stress among boarding school students.